Auditoría de gestión financiera en la ferretería bycace del cantón Latacunga, provincia de Cotopaxi durante el periodo 01 de enero al 31 de diciembre del 2013 - Mena Zapata, Gustavo Patricio (2015)
One of the problems in the process of developing the economy of a hardware store is the difficulty of knowing the magnitude of inventory items, tools and building materials. To know and evaluate the problems to determine the causes hindering the business of an organization, so it is necessary to apply an Audit of Financial Management that allows measuring the degree of objectives compliance, plans, programs and a private business goals with the purpose to ensure proper use of resources in terms of efficiency, effectiveness and ethics. For this research the investigator applied collections methods such as: the observation, the interview, survey applied to the Hardware personnel….